Clinicopathological features of Lynch syndrome pedigrees with MSH2 c.351G>A gene variant - Shuai Zhang; Guanyu Fu; Gongping Sun; Yuanxin Tang; Jin Meng; Zhigang Wang; Rongjun Su; Wei Liu; Xiaoxia Li (Molecular Genetics & Genomic Medicine)
Abstract Background Lynch syndrome (LS) is an autosomal‐dominant disorder that increases the risk of many cancers. To identify novel or rare pathogenic variants of MMR genes associated with LS, especially in Chinese pedigrees. Methods One four‐generation Chinese Han family from northeast China with 29 members was enrolled. Clinical diagnosis of LS was established in this family, according to Amsterdam II. The proband and some relatives of the family were subjected to immunohistochemical analysis of MMR protein, microsatellite instability (MSI) testing, whole‐exome sequencing, and Sanger sequencing. Results Nine patients with 19 primary cancers were found in this family, with a wide spectrum of synchronous and metachronous cancers, including digestive, reproductive, respiratory, urinary, and other systems. In addition, one member of this family is found to have both thyroid and lung cancers, which have been reported only once in LS patients before but have not been considered extracolonic in the LS spectrum. The immunohistochemical analysis of the mother of the proband showed loss of MSH2 and MSH6 protein, and consistently, high microsatellite instability (MSI‐H) was confirmed in LS patients. Furthermore, whole‐exome sequencing identified a nonsense variant in MSH2, MSH2:NM_000251:c.351G > A(p.W117*), in all three tested LS patients (II‐1, III‐1, and III‐4), but not in healthy relatives IV‐1 in this family. This result is further verified by Sanger sequencing. Conclusion Uncover a rare nonsense variant in MSH2 gene, which contributes to LS of this family. The clinicopathological characteristics of LS in this family include common simultaneous or heterogeneous multiple primary cancers, a broad tumor spectrum, and a younger age with the continuation of genetic algebra.